A hospital based cross-sectional study on clinical profile of patients with spinal cord injuries - G Krishnamurthy; Goutham Kumar (MRIMS Journal of Health Sciences, 2020)
Background: Correct incidence of the spinal cord injuries in India is not known. Prevention is better than cure as there is no proper cure for the spinal cord injuries. Hence, study of clinical profile of patients with spinal cord injuries is required. Objectives: The present study was undertaken to study the clinical profile of spinal cord injuries in tertiary care hospital in rural area. Materials and Methods: This was a hospital-based cross-sectional study conducted among 56 patients with spinal cord injuries. Detailed history, required investigations were recorded. The data was analyzed using proportions. Results: Younger age groups from 20 to 49 were more commonly affected than older age group of 50 years and above. The most common site of spinal cord injuries was at the level of thorax (64.3%) followed by lower cervical level in 21.4% of the cases. 39.2% of the study subjects had complete spinal cord injury and 60.8% had incomplete spinal cord injury. Majority had both variety of injuries in the thoracic cord. Conclusion: It can be concluded that spinal cord injuries are common in the younger age group, thoracic site being the most common for injury and incomplete type of injury is common.